THE RELATIONSHIP OF OBESITY WITH RISK OF DEMENTIA IN OLDER AGE - Risma Yunita; Lina Indrawati; Baltasar Serilus Sanggu Dedu (Journal of Vocational Nursing)
Introduction: Obesity has become a pressing global health concern in recent years, affecting individuals of all ages and backgrounds. While the detrimental effects of obesity on physical health are well-documented, its impact on cognitive function, particularly in the elderly population, is a growing area of concern. In recent research studies, a compelling association has been established between obesity and an increased risk of dementia among older adults. Purpose: To determine the relationship between obesity and the risk of dementia in the elderly. Methods: This research is a quantitative study with analytical descriptive methods with a cross-sectional study approach. The sample in this study used purposive sampling totaling 35 samples with the criteria of obese elderly people who did not have chronic diseases. This research instrument used a Body Mass Index (BMI) filling sheet and a Mini-Mental State Examination (MMSE) observation sheet and the analysis used was Chi-Square. Results: Based on statistical tests, the p-value obtained was 0.049 with (p < 0.05), which means Ha is accepted, meaning there is a relationship between obesity and the risk of dementia in RT 01-03 RW 07, Margamulya Village, North Bekasi District, Bekasi City. 2023. Conclusion: Old age and elderly women have the greatest risk factors for developing dementia, the main cause of obesity and the risk of developing dementia is low physical activity in the elderly, so the relationship between obesity and the risk of dementia is obesity as a cause of comorbid diseases. causes vascular disorders in the brain, causing dementia.